Fas ligand-transfected myoblasts and islet cell transplantation. - Turvey, SE; Gonzalez-Nicolini, V; Kingsley, C; Larregina, A; Morris, P; Castro, MG; Lowenstein, P; Wood, K (2000)
BACKGROUND: Expression of Fas ligand (FasL, CD95L) within the local environment of an allograft may protect from rejection by inducing apoptosis of infiltrating T cells. However, there is mounting evidence that ectopic expression of FasL stimulates an inflammatory response and targets the FasL-expressing tissue for destruction. Given the potential therapeutic applicability of FasL-based immune protection, we sought to determine whether ectopic FasL expression was detrimental and to analyze the inflammatory response induced by ectopic FasL expression in the absence of any confounding allo-immune responses. METHODS AND RESULTS: Two myoblast cell lines expressing different levels of functional FasL were produced. Co-implantation of FasL-expressing myoblasts with syngeneic islets allowed examination of the inflammatory response induced by ectopic FasL expression. In contrast to the suggested benefits of localized FasL expression, islets co-implanted with FasL-expressing myoblasts were destroyed in a vigorous inflammatory response predominated by neutrophils. Interestingly, FasL expression also had a marked anti-tumor effect. CONCLUSIONS: Unless FasL-dependent neutrophil-mediated inflammation can be prevented, it is unlikely that this strategy will be useful for preventing allograft rejection.